2005
DOI: 10.21608/ejabf.2005.1816
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Some Heavy Metals in Tissues of Oreochrom1s Siloticus* Tilap1a Zjll11 and Clarias Lazera From Abu Za'baal Lakes and Their Impacts on Some Biochemical Parameters and on the Histological Structures of Some Organs

Abstract: A bu Za'baal Lakes are man-made lakes, formed by the fracture apd extract of rocks. The lakes, as other inland closed basins. receive their water from the ground and seepage waters. They consist of three lakes and another filling-phase lake. In the present study, the concentrations of some heavy metals {Fe. Zn. Mn. Pb. Cu and Cd) in water and organs (muscles, gills, liver and kidney) of O. niloticus. T, zillii and C. iazera collected from Abu Za'baai Lakes were measured during winter. 2004. The effects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
5
6
0
Order By: Relevance
“…It was found that Fe concentration recorded higher accumulation in the muscle than the water during the winter season. Higher Fe content in muscle of O.niloticus can be attributed to the large quantities of Fe in water , this agree with the findings of Ghazaly et al (1992) , Tariq et al (1993 , Bahnasawy (2001) and Mohamed and Gad (2005). Iron concentrations in the water and muscle of fish is more than the maximum permissible level for Fe (5.0mg/g) cited by Abeyede (1993).…”
Section: Resultssupporting
confidence: 89%
“…It was found that Fe concentration recorded higher accumulation in the muscle than the water during the winter season. Higher Fe content in muscle of O.niloticus can be attributed to the large quantities of Fe in water , this agree with the findings of Ghazaly et al (1992) , Tariq et al (1993 , Bahnasawy (2001) and Mohamed and Gad (2005). Iron concentrations in the water and muscle of fish is more than the maximum permissible level for Fe (5.0mg/g) cited by Abeyede (1993).…”
Section: Resultssupporting
confidence: 89%
“…The results indicated that the present level of the examined heavy metals in water and fish muscles from Abu Za'baal lakes did not exhibit any effect on proximate composition and physicochemical characteristics of fish muscles. This result is in agreement with (Abdo, 2006, Ibrahim et al, 2008& Mohamed and Gad 2005.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, lipid content varies within species (1.46-5.77 g/100g) and is affected by the catching season (1.20-18.4 g/100g), (Osman, et al, 2001). Mohamed and Gad (2005) proved that, protein and lipid contents in the tissue of Oreochromis niloticus and Clarias lazera from Abu Za'baal lakes were (15.95-15.87) and (0.96-0.99) g/100 g wet weight, respectively. Osibona et al, (2006) found that Clarias gariepinus had mean protein content of 19.64%, lipid 1.15%, moisture 76.71% and ash 1.23%.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have been carried out on these lakes and lights were thrown on morphometry and bathymetry (Abd-Ellah, 2003), physico-chemical characteristics (Abdo, 2005), pathological conditions of Tilapia zillii (El-Mansy, 2005), phytoplankton composition (Mohamed, 2005), metals accumulation in fish organs (Mohamed and Gad, 2005), microbiological status (Rabeh and Azab, 2006), zooplankton community (El-Basset and Taylor, 2007),biological, histological and quality aspects of fish (Ibrahim et al 2008), reproductive biology of O.niloticus, and feeding habits of O.niloticus (Shalloof and Khalifa, 2009). The objective of study was to provide and update information on the growth and feeding habits needed by cichlid species to flourish in these newly formed mining lakes.…”
Section: Introductionmentioning
confidence: 99%